The Medical Healing of Souls: a strategy for welcoming post-pandemic mental health - Angelica Yolanda Bueno Bejarano Vale de Medeiros; Eliane Ramos Pereira; Rose Mary Costa Rosa Andrade Silva (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to reflect on the applicability of the Medical Healing of Souls (MHS) by health professionals as a welcoming strategy in post-pandemic mental health. Methods: a theoretical and reflective study, based on Viktor Frankl's philosophy, based on the book "The Doctor and the Soul, From Psychotherapy to Logotherapy" and scientific literature. Results: the study was structured in two discursive approaches: MHS in the field of health; The applicability of MHS in post-pandemic mental health care. Final considerations: MHS can be used in mental health care, in health emergencies, promoting a more humane performance of health professionals, facilitating the integration of inevitable suffering into a meaningful life.